Methodology for studying linkage effects of agricultural modernization - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The document explains that analyzing impacts of the agricultural modernization of a subsector on the overall economy is one focus of IICA research. Phase I provided insights into modernization in eight subsectors, and phase II will address the issue of spinoffs in a more detaile and structured manner. Phase I of this project began the process of identifying the elements of a successful modernization effort. To expand this analysis and provide more detailed evidence of results, research in Phase II must focus on understanding the dimensions of modernization spinoffs on two levels; i) assessing the impact on the economy, and ii) establishing the process of modernization which brought about those end results. Industrial organizations trade environment and fiscal regime; and external market arrangements. Phase III presents flowcharts, questionnaires anb data. Phase IV the selection of cases, and the V the outputs of case studies. Six annexes are included: summary of methodology; flowcharts; farm level questionnaire; industry level questionnaire; marketing questionnaire and case study comparison matrix.